Metal-mask configurable RF front-end circuits. - Yang Xu (IEEE Journal of solid state circuits)
This paper describes metal-mask configurable RF circuits using a base circuit fabric that can be configured for various wireless applications using only upper metal and via layers. This front-end circuit fabric achieves a wide range of configurability (e.g., operating center frequency) and is essentially applicable for any IC technology. The prototype RF front-end circuit fabric was designed to be configurable for GPS at 1.5 GHz, W-CDMA at 2.1 GHz and WLAN at 5 GHz in a 0.25-μm 47-GHz fT SiGe BiCMOS process. The upper three metal and via layers are the only application-specific layers for the three applications. The front-end circuits draw 10.5, 9.5, and 8.5 mA from a 2.5-V supply, respectively, at 1.5, 2.1, and 5 GHz while providing a noise figure of 2.5, 2.8, and 4.5 dB, conversion gain of 24.6, 24.2, and 12 dB, and IIP3 of -8, -9, and -4 dBm, respectively.